2007
DOI: 10.1112/plms/pdm021
|View full text |Cite
|
Sign up to set email alerts
|

Higher correlations of divisor sums related to primes III: small gaps between primes

Abstract: We calculate the triple correlations for the truncated divisor sum λ R (n). The λ R (n) behave over certain averages just as the prime counting von Mangoldt function Λ(n) does or is conjectured to do. We also calculate the mixed (with a factor of Λ(n)) correlations. The results for the moments up to the third degree, and therefore the implications for the distribution of primes in short intervals, are the same as those we obtained (in the first paper with this title) by using the simpler approximation Λ R (n).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 30 publications
3
82
0
2
Order By: Relevance
“….. Maier's method had the shortcoming that it produced a sparse set of gaps; prior authors had shown that small gaps occur in a positive proportion of all cases. Goldston and Yıldırım [9] proved the upper bound of 0.25 for a positive proportion of gaps. Recently, the first, third and fourth authors proved a best possible result in this direction.…”
Section: Small Gaps Between Primes 5287mentioning
confidence: 99%
“….. Maier's method had the shortcoming that it produced a sparse set of gaps; prior authors had shown that small gaps occur in a positive proportion of all cases. Goldston and Yıldırım [9] proved the upper bound of 0.25 for a positive proportion of gaps. Recently, the first, third and fourth authors proved a best possible result in this direction.…”
Section: Small Gaps Between Primes 5287mentioning
confidence: 99%
“…Green and Tao in [85] credit Andrew Granville for pointing them to the preprint [72]. The correlation estimates therein, with relatively minor changes, were sufficient to prove that ν was pseudorandom in the sense of [85].…”
Section: The Sum-product Problemmentioning
confidence: 96%
“…Objects of this type were extensively analysed by Goldston and Yıldırım [11,12,13], and in particular they saw how to asymptotically evaluate certain correlations of the form (8.1) provided R N cm . This was a crucial ingredient in our work in [18], but we should remark that other aspects of the function β R were investigated much earlier, and indeed β R was known to Selberg.…”
Section: Appendix: a Comparison Of Two Enveloping Sievesmentioning
confidence: 99%
“…We note that results along the lines of Theorem 1.2 can be approached using sieve methods and the Hardy-Littlewood circle method in a more classical guise. For example, Tolev [33] showed that there are infinitely many 3-term progressions p 1 < p 2 < p 3 of primes such that p i + 2 is a product of at most r i primes, where (r 1 , r 2 , r 3 ) can be taken to be (5,5,8) or (4,5,11).…”
mentioning
confidence: 99%